CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS PERUSAHAAN PERBANKAN DI INDONESIA - Utari, I Gusti Ayu Diah; Pramitari, I Gusti Ayu Astri; Yunita, Ni Putu Maysia Sutiasih (Buletin Studi Ekonomi, 2021)
The purpose of this research is to look into the impact of Corporate Social Responsibility (CSR) on profitability (ROA). Corporate Social Responsibility (CSR) is measured by the costs of environmental development, partnerships, and employee welfare. This study employs 45 banking sector companies listed on the Indonesian stock exchange from 2017 to 2019, with a total sample of 42 drawn from a purposive sampling technique. The financial statements issued by the company each year are the source of the data. Multiple regression analysis methods are used in data analysis. According to this study, the cost of environmental development will reduce the company's profitability. The same is true for the relationship between partnership costs and employee welfare costs and the profitability of Indonesia Stock Exchange-listed banking companies in 2017-2019.